Population Aging and Economic Growth: Will the population aging reduce household saving in China? - Zhu, Xun (Université d'Ottawa | University of Ottawa, 2015)
Over the next three decades, from 2010 to 2040, China is projected to have a population increase of 15.7 percent in its population aged 60 years or over. This dramatic increase would be the fastest in the world. One of the likely major consequences of this demographic transition is a downward pressure on household saving rates as the life cycle hypothesis (LCH) suggests. This paper uses a household saving model to analyze the effects of demographic factors on household saving rates in China. The regression results suggest that the increasing proportion of elders in China would have a positive impact on household saving rate. This finding implies that the population aging transition in China would not put a downward pressure on household savings and hence on economic growth.